Analysis of Factors Influencing Consumer Purchasing Decisions at Culinary Micro Small and Medium Enterprises Centers in Sidoarjo Square - Endang Siswati; Juliani Pudjowati (Universitas Islam Lamongan, 2023)
This study aims to analyze what factors influence consumer purchasing decisions at culinary MSME centers in Sidoarjo square, and what are the stages, with a qualitative descriptive approach. The analytical method uses data reduction, presentation and conclusion. The results of the study found that consumer purchasing decisions were influenced by cultural factors, social factors of family togetherness enjoying culinary delights, psychological factors of consumers, namely purchase motivation based on needs, as well as perceptions about product, price, and taste. The stages in the consumer buying decision process are based on: the existence of a need, seeking information from family, friends, and the media, then evaluating several alternatives, then the buying decision stage. repeat purchase is based on customer satisfaction